Remote sensing investigation of spatiotemporal land-use changes: A case study of Batticaloa town in sri lanka from 1979 to 2021 - Partheepan, Kulasegaram; Musthafa, Muneeb M.; Bhavan, Thangamani (TeMA - Journal of Land Use, Mobility and Environment, 2023)
<span class="NormalTextRun SCXW38286821 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn=""ObjectId":"c3dc37e2-6900-4b2f-87e2-318eaa5b9f6d|107","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"39",335572020,"0",201342448,"1",469777841,"Tahoma",469777842,"Tahoma",469777843,"Calibri",469777844,"Tahoma",469769226,"Tahoma,Calibri",268442635,"18",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]">Rapid and haphazard urbanization has disastrous environmental and socio-economic consequences. The increase of unofficial habitation characterizes urbanization in Batticaloa town. Urban land use and cover changes require research to plan and ensure long-term growth. This study employed geographic information systems and Landsat imagery from 1979, 2000, and 2021 to look at regional and temporal variations in Batticaloa’s land use cover. A support vector machine and supervised classification constructed the land use cover maps. The transition matrices produced from the classified map were further investigated to find the essential change processes for prioritizing planning, and during the 42 years investigated, built-up, including residential, commercial, and public facilities, increased in a similar vein (i.e., mangroves, paddyland, vegetation-covered areas, and shrubs). Land use cover modifications happened more quickly between 2000 and 2021 than between 1979 and 2000. The analysis found that only one land-use category, net built-up area changes, grew by 8.2%, and the average yearly change was 0.22%. By 21.9%, paddy land area substantially increased. Bare lands rose 4.45%, and thick woods fell 21.37%. These data show built-up areas frequently targeted bare terrain. This research laid the groundwork for long-term urban planning and development in Batticaloa Town.